Using computer modeling to find new LRRK2 inhibitors for parkinson’s disease - María C. García; Sebastián A. Cuesta; José R. Mora; Jose L. Paz; Yovani Marrero-Ponce; Frank Alexis; Edgar A. Márquez (Scientific Reports)
Abstract Parkinson’s disease (PD) is a complex neurodegenerative disorder that affects multiple neurotransmitters, and its exact cause is still unknown. Developing new drugs for PD is a lengthy and expensive process, making it difficult to find new treatments. This study aims to create a detailed dataset to build strong predictive models with various machine learning algorithms. An ensemble modeling approach was employed to screen the DrugBank database, aiming to repurpose approved medications as potential treatments for Parkinson’s disease (PD). The dataset was constructed using pIC50 values of various compounds targeting the inhibition of leucine-rich repeat kinase 2 (LRRK2). The best ensemble model showed exceptional predictive performance, with five-fold cross-validation and external validation metrics exceeding 0.8 (Q2cv = 0.864 and Q2ext = 0.873). The DrugBank screening resulted in three promising drugs—triamterene, phenazopyridine, and CRA_1801—with predicted pIC50 values greater than 7, warranting further investigation as novel PD treatments. Molecular docking and molecular dynamics simulations were performed to provide a comprehensive understanding of the interactions between LRRK2 and the inhibitors in the data set and best molecules of the screening. Free energy of binding calculation along with hydrogen bond occupancy analysis and RMSD of the ligand in the pocket show CRA_1801 as the best candidate to be repurposed as LRRK2 inhibitor.